Pilot Physical Activity Intervention Reduces Severity of ADHD Symptoms in Young Children. (January 2013) - Smith, Alan L.; Hoza, Betsy; Linnea, Kate; McQuade, Julia D.; Tomb, Meghan; Vaughn, Aaron J.; Shoulberg, Erin K.; Hook, Holly
Objective: Physical activity associates with mental health and neurocognitive function, showing potential for addressing ADHD symptoms. As a preliminary assessment of this potential, the authors piloted a before-school physical activity intervention for young children.Method: Seventeen children (Grades K-3) exhibiting four or more hyperactivity/impulsivity symptoms on the Disruptive Behavior Disorders Rating Scale (Pelham, 2002) completed about 26 min of continuous moderate-to-vigorous physical activity daily over eight school weeks. The authors administered cognitive, motor, social, and behavioral functioning measures at pre- and postprogram, assessed response inhibition weekly, and coded negative behaviors daily.Results: Several measures showed significant or marginally significant change over time (effect size = 0.35-0.96) with additional measures showing meaningful effect size values (≥ 0.20). Response inhibition effects were most consistent. Most participants (64% to 71%) exhibited overall improvement according to postprogram parent, teacher, and program staff ratings.Conclusion: Physical activity shows promise for addressing ADHD symptoms in young children.